Handbuch der Kulturgeschichte - Thurnher, Eugen; Kindermann, Heinz (Akad. Verl.-Ges. Athenaion, 1956)
Vorkriegsausg. s. idn 4629630
Verl.-Ort wechselt. - Urspr. hrsg. von Heinz Kindermann
Keywords: Geschichte; Kultur